ANALISIS DETERMINAN PERKEMBANGAN EKSPOR TEKSTIL DAN PRODUK TEKSTIL INDONESIA - Paradita, Buya Ary; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2018)
The purpose of this study is to determine the effect of competitiveness, exchange rate and GDP simultaneously and partially to the development of Indonesian textile and textile product exports. Research is conducted in Indonesia as a research location because export competitiveness can only be measured on a national scale. Analytical techniques used were RCA, RSCA and multiple linear regression analysis. Based on the results of RSCA calculations obtained that in the year 1990-2004 the value of RSCA <0 means that the state of Indonesia does not have a comparative advantage in textile commodities and textile products. In 2005-2015 the value of RSCA ? 0, thus in that year Indonesia has a comparative advantage in textile and textile products. Competitiveness, exchange rate and GDP simultaneously affect the development of Indonesian textile and textile products export from 1990-2015. It can be seen that competitiveness, exchange rate and GDP significantly partially influence the development of Indonesian textile and textile products export from 1990-2015. Keywords: competitiveness, exchange rate, GDP, development of textile exports and textile products.